CAR T-cells for T-cell malignancies: challenges in distinguishing between therapeutic, normal, and neoplastic T-cells. Issue 11 (November 2018) - Alcantara, Marion; Tesio, Melania; June, Carl; Houot, Roch
Abstract Chimeric antigen receptor (CAR) T-cells targeting CD19 demonstrated remarkable efficacy for the treatment of B-cell malignancies. The development of CAR T-cells against T-cell malignancies appears more challenging due to the similarities between the therapeutic, normal and malignant T-cells. The obstacles include CAR T-cell fratricide, T-cell aplasia, and contamination of CAR T-cell products with malignant T-cells. Here, we review these challenges and propose solutions to overcome these limitations.